CBX4 Provides an Alternate Mode of Colon Cancer Development via Potential Influences on Circadian Rhythm and Immune Infiltration - Wei, Wangzhi; Zhao, Wei; Zhang, Yu (Frontiers in Cell and Developmental Biology, 2021)
The circadian machinery is critical for the normal physiological functions and cellular processes. Circadian rhythm disruption has been associated with immune suppression which leads to higher cancer risk, suggesting a putative tumor protective role of circadian clock homeostasis. CBX4, as an epigenetic regulator, has been explored for its involvement in tumorigenesis. However, little is known about the correlation between CBX4 and circadian rhythm disruption in colon cancer as well as the potential impact on the tumor immunity. A significant upregulation of CBX4 was identified in the TCGA colon adenocarcinoma (COAD) samples when compared with the normal controls (p<0.001). This differential expression was confirmed at the protein level using colon adenocarcinoma tissue array (p<0.01). CBX4 was up-regulated in the recurred/progressed colon cancer cases compared with the disease-free samples (p<0.01), suggesting CBX4 as a potential predictor for poor prognosis. With regard to nodular metastasis, CBX4 was found to be associated with early onset of metastatic diseases but not late progression. The circadian rhythm is orchestrated by the alternating activation and suppression of the CLOCK/ARNTL-driven positive loop and the PER/CRY-controlled negative loop. In COAD, CBX4 was negatively correlated with CLOCK (p<0.001), and positively correlated with PER1 (p<0.001), PER3 (p<0.01) and CRY2 (p<0.001) as well as NR1D1 (p<0.001), a critical negative regulator of the circadian clock (p<0.001). These interactions consistently impacted on patient survival based on the colorectal cancer cohorts GSE17536 and GSE14333 of PrognoScan. CBX4 showed significant negative correlations with infiltrating B cells (p<0.05) and CD4+ T cells (p<0.01), and positive correlations with myeloid derived suppressor cells (MDSCs) (p<0.05) and cancer associated fibroblast (CAFs) (p<0.001), as well as a low immunoscore. Moreover, CBX4 displayed significant correlations with diverse immune metagenes. PER1 and PER3, consistent with their coordinated expression with CBX4, also had strong correlations with these gene representatives in COAD, suggesting a potential interaction of CBX4 with the circadian machinery. Our studies implicate that CBX4 may contribute to colon cancer development via potential influence on circadian rhythm and immune infiltration. These findings provide new insights into deciphering the function of CBX4, and may contribute to the development of new targeting strategies.